Digital silence as a pragmatic strategy: An intercultural qualitative study of online group chats in crisis situations - Abdullah, Ahmed Subhi (Journal of Social, Humanity, and Education, 2025)
Purpose: This study investigates digital silence as a pragmatic strategy in online group chats during crisis situations, focusing on its cross-cultural functions and interpretations. Research methodology: Using a qualitative discourse-pragmatic framework, data were collected from 30 online group chats across Arabic-speaking, Western, and East Asian groups, and analyzed for patterns of silence. Results: Findings reveal that digital silence is universally used but culturally interpreted. In Arabic-speaking groups, silence often conveys politeness or emotional overwhelm; in Western contexts, it may suggest avoidance; and in East Asian cultures, it can indicate deference or restraint. Conclusions: Digital silence operates as a strategic communicative act shaped by cultural expectations. This study addressed three research questions. First, digital silence is used pragmatically in online group chats during crises to convey politeness, emotional regulation, resistance, and ambiguity. Second, it serves functions such as mourning, face-saving, strategic withdrawal, and deference. Third, these functions vary culturally: in Arabic-speaking contexts, silence often reflects solidarity and emotion; in Western groups, it can imply resistance or discomfort; and in East Asian settings, it demonstrates restraint and hierarchy. Limitations: The research is limited to group chats during specific types of crises, and findings may not generalize to all online interactions. Contribution: This study contributes to digital pragmatics and intercultural communication by illuminating the nuanced role of silence in crisis discourse.